The Effect of a Process Image-Based Electromagnetic Induction Module on Senior High School Students' Mastery of Concepts and Critical Thinking Skills in Physics - Febrianty, Wanda; Sutarto, Sutarto; Harijanto, Alex; Indrawati, Indrawati (UNIVERSITAS INDRAPRASTA PGRI, 2025)
This research aims to examine the effect of an electromagnetic induction module based on process images on high school students' conceptual mastery and critical thinking skills in physics. The research design used is a nonequivalent control group design with cluster random sampling. This research was conducted at SMA Negeri Arjasa Jember in the second semester of the 2024/2025 academic year. The sample consisted of one experimental class and one control class. Data were collected through pretests, posttests, and observations. The analysis of conceptual mastery using the Mann-Whitney U Test showed a significance value of 0.020 (2-tailed) and 0.010 (1-tailed), indicating a significant effect of the module on conceptual mastery. Meanwhile, the analysis of critical thinking skills showed a significance value of 0.519 (2-tailed), indicating that the module did not significantly affect students' critical thinking skills. These findings suggest that the module effectively supported students' conceptual understanding but was insufficient to foster higher-order thinking. The results highlight the need to integrate more inquiry-based or reflective activities into future module designs to better promote critical thinking skills.